(untitled) (Research, Society and Development, 2022)
The packaging industry requires materials capable of offering barriers to the entry of microorganisms, with the ability to protect and maintain the characteristics of the packaging content. The use of fillers can enhance these barrier properties to the polymeric material. This work investigates the effect of incorporating different fillers (organophilic clay and corn straw) on the rheological, thermal, mechanical and permeability characteristics of polycaprolactone (PCL) processed in an internal laboratory mixer. The results of torque rheometry suggest polymer matrix degradation during processing did not increase, nor the thermal stability of the matrix. Composite films showed higher tensile strength, higher stiffness and lower elongation. Incorporation of the fillers in the PCL matrix reduced the permeability to oxygen and carbon dioxide gases of the produced films. Adding up to 1% of organoclay C20A or corn straw to PCL leads to a material that combines maintenance or improvement of properties combined with lower permeability to oxygen and carbon dioxide, which confirms the potential use of these systems in packaging industry.